Correlation of nodule with body mass index and Karnofsky status in nasopharyngeal carcinoma chemotherapy - Bagus Harning Efranto; Soehartono -; Edi Handoko (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy arising from the nasopharyngeal epithelium, usually present in the Rosenmüller fossa. NPC is a cancer of the head and neck that is most common in Indonesia. The main therapeutic for NPC is radiotherapy. Neoadjuvant chemotherapy reduces the local spread of advanced NPC, optimizing the eradication of micrometastases, and improved local control. Neoadjuvant chemotherapy’s effectiveness can be assessed by changes in the patient’s neck nodule size (N), Body Mass Index (BMI), and Karnofsky’s status. Purpose: To determine the correlation between N with BMI and Karnofsky status on neoadjuvant chemotherapy with Cisplatin and 5-Fu in WHO type 3 of NPC patients. Method: Analytical observational study using medical record data. An assessment of N, BMI and Karnofsky status of NPC WHO type 3 of 23 patients who had undergone neoadjuvant chemotherapy using Cisplatin and 5-Fu for three cycles. Result: The N value decreased, p = 0.001. BMI value decreased, p = 0.615. Karnofsky’s status value, p = 0.564. The correlation between N and BMI before and after three cycles of neoadjuvant chemotherapy: r = -0.201 and p = 0.358 ; r = -0.070 and p = 0.751. Correlation of N with Karnofsky status: r = 0.155 and p = 0.480; r = 0.571 and p = 0.004. Conclusion: Neoadjuvant chemotherapy with Cisplatin and 5-Fu was effective towards reducing the N and also in correlation between N and BMI but less effective in the correlation between N and Karnofsky status.ABSTRAK Latar belakang: Karsinoma nasofaring (KNF) adalah keganasan yang berasal dari epitel nasofaring yang biasanya timbul di fossa Rosenmüller. KNF merupakan kanker di kepala dan leher yang paling umum terjadi di Indonesia. Terapi utama pada KNF adalah radioterapi. Kemoterapi neoajuvan dapat menurunkan penyebaran lokal KNF stadium lanjut, mengoptimalkan eradikasi mikrometastasis, dan meningkatkan kontrol lokal. Efektivitas kemoterapi neoajuvan dapat dinilai dengan perubahan ukuran nodul leher (N) pasien, indeks massa tubuh (IMT) dan status Karnofsky pasien. Tujuan: Mengetahui korelasi antara N dengan IMT dan status Karnofsky pada pemberian kemoterapi neoajuvan Cisplatin dan 5-Fu pada pasien KNF WHO tipe 3. Metode: Penelitian observasional analitik dengan menggunakan data rekam medis. Penilaian dilakukan terhadap N, IMT dan status Karnofsky pada 23 pasien KNF WHO tipe 3 yang telah menjalani kemoterapi neoajuvan dengan menggunakan Cisplatin dan 5-Fu sebanyak tiga siklus. Hasil: Nilai N menurun, p=0,001. Nilai IMT menurun, p=0,615. Nilai status Karnofsky, p=0,564. Korelasi antara N dengan IMT sebelum dan setelah tiga siklus kemoterapi neoajuvan: r= -0,201 dan p= 0,358; r= -0,070 dan p=0,751. Korelasi N dengan status Karnofsky: r=0,155 dan p=0,480; r=0,571 dan p=0,004. Kesimpulan: Kemoterapi neoajuvan dengan Cisplatin dan 5-Fu efektif terhadap penurunan N serta korelasi antara N dengan IMT, namun kurang efektif menilai korelasi antara N dengan Status Karnofsky.Kata kunci: karsinoma nasofaring, kemoterapi neoajuvan,nodul, indeks massa tubuh, status Karnofsky